2008
DOI: 10.1111/j.1365-2621.2007.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preliminary and culinary processing on amino acid content and protein quality in frozen French beans

Abstract: The aim of the study was to evaluate the content of amino acids and protein quality of French bean pods. The investigated material consisted of the raw vegetable, fresh pods cooked to consumption consistency, and two kinds of frozen products stored for 12 months at )20°C and then prepared for consumption: frozen beans obtained using the traditional method (blanching before freezing) and frozen products of the ready-toeat type (cooking before freezing). A comparison of the amino acid content in the product prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This proportion is comparable with other vegetable species : 44% in kale (Lisiewska et al. , 2008); 41% in French bean (Kmiecik et al. , 2008); and 36% in Brussels sprouts (Lisiewska et al.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This proportion is comparable with other vegetable species : 44% in kale (Lisiewska et al. , 2008); 41% in French bean (Kmiecik et al. , 2008); and 36% in Brussels sprouts (Lisiewska et al.…”
Section: Resultssupporting
confidence: 68%
“…Different amino acids are lost in different plants probably because of differences in their structural composition and susceptibility to destruction by heat (Ziena et al. , 1991; Kmiecik et al. , 2008; Lisiewska et al.…”
Section: Resultsmentioning
confidence: 99%
“…In the instant whole beans obtained in this study, 75 % of the essential amino acids (lysine, threonine, isoleucine, valine, leucine, phenylalanine and tyrosine) had EAA=essential amino acids, NEAA=non-essential amino acids, CS=chemical score, EAAI=essential amino acid index, PER=protein effi ciency ratio a value greater or equal to the reference standard for adults (20), while the tryptophan and sulphur-containing amino acids (methionine and cysteine) were the limiting amino acids, as it has been observed in other bean varieties and legume seed protein isolates (37,38). In contrast, the protein quality of instant whole beans in terms of chemical score was 95 %, in comparison with the values of 80-82 % reported for other varieties of cooked beans (37,39), while the essential amino acid index was 104.1 %, indicating a high nutritive value of the protein but lower than the reported values of 112-115 % for raw and processed French beans (40 …”
Section: Drying Of Cooked Beansmentioning
confidence: 41%
“…The present authors agree that changes in the level of amino acids are not only determined by the pre-treatment parameters but also by the species in question and the edible parts of the vegetable, i.e. the particular tissue under investigation (Klein and Mondy 1981, Murcia et al 2001, Kmiecik et al 2008b, Kmiecik et al 2009. The literature shows that the retention of amino acids varies depending on the factors mentioned above: statistically significant losses may be found (Candela et al 1997, Diasolua-Ngudi et al 2003; but also, as in the present investigation, no significant changes might be observed (Khalil and Mansour 1995, Murcia et al 2001, El-Adawy 2002, Korus et al 2003; or, as reported by Mutia and Uchida (1993), the content of amino acids in edible parts may increase significantly.…”
Section: Resultsmentioning
confidence: 62%
“…The highest EAA index characterizing protein quality was registered by raw cauliflower (117), followed by the product from traditionally frozen cauliflower (114), with the lowest found in the remaining samples (106). The limiting amino acid in the protein of various vegetable species is usually methionine with cystine (Choi and Lee 1999, Diasolua-Ngudi et al 2003, Korus et al 2003, Kmiecik et al 2008b, though it may also be lysine (Ishida et al 2000, Ayaz et al 2006, histidine (Lopez et al 1996) or tyrosine with phenylalanine (Kmiecik et al 2009). …”
Section: Resultsmentioning
confidence: 99%